TINJAUAN KEMBALI SEJARAH SULAWESI SELATAN (ABAD IX - XIV M) BERDASARKAN BEBERAPA SUMBER TERTULIS - Budianto Hakim (BRIN, 1994)
The journey of fifteen centuries in the coverage of ancient history is quite a long period of time. In an effort to reveal this history, it is seen that there are gaps such as a description of time, a description of the situation of each section, as well as the aspect of the area being discussed. This situation occurs as a result of unequal historical and archaeological research in the archipelago. The research that has been carried out is generally focused on the history of areas that have left a lot of cultural evidence, especially with regard to Hindu cultural heritage such as in Java. Sumatra, Kalimantan and Bali. Meanwhile, ancient historical research for other areas is still lacking, such as in South Sulawesi.